2018
DOI: 10.3892/ijmm.2018.3963
|View full text |Cite
|
Sign up to set email alerts
|

The short-term effect of histone deacetylase�inhibitors, chidamide and valproic acid, on�the�NF‑κB�pathway in multiple myeloma cells

Abstract: Research regarding histone deacetylase (HDAC) inhibitors (HDACis) has garnered interest for the treatment of multiple myeloma (MM). In addition, the high expression of nuclear factor (NF)-κB in MM cells is considered an important factor in the occurrence and development of MM. The present study aimed to determine the short-term effects of HDACis, chidamide and valproic acid (VPA), on MM cells, their effects on NF-κB and the underlying mechanisms. The present study measured HDAC activity, and the proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Thus, it is urgent demand to develop novel drugs against MM. CHI, a novel orally HDACi has been approved by the CFDA for the treatment of PTCL 14 , was found to be potential therapeutic agent in MM in vitro and in vivo 15 , 17 , 27 . In the present study, we showed for the first time that combination of CHI and BTZ significantly increased cell death compared with CHI or BTZ alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is urgent demand to develop novel drugs against MM. CHI, a novel orally HDACi has been approved by the CFDA for the treatment of PTCL 14 , was found to be potential therapeutic agent in MM in vitro and in vivo 15 , 17 , 27 . In the present study, we showed for the first time that combination of CHI and BTZ significantly increased cell death compared with CHI or BTZ alone.…”
Section: Discussionmentioning
confidence: 99%
“…As an epigenetic modulator, CHI induced tumor cell growth arrest and apoptosis and enhanced cellular antitumor immunity [12][13][14]. CHI exhibited significant cytotoxicity against MM cells co-cultured with bone mesenchymal stromal cells and CHI-pretreated osteoclasts in recent studies [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…HDAC-inhibiting and anti-myeloma activities of chidamide have been demonstrated in MM. 25,[28][29][30] It has been reported that HDAC inhibitor vorinostat increased the levels of ROS in drug-resistant cells, which caused selective apoptotic death of only the drug-resistant tumour cells. 15 Thus, we speculated that the overproduction of ROS may be responsible for the anti-myeloma activity of chidamide.…”
Section: Discussionmentioning
confidence: 99%
“…Chidamide also inhibits pancreatic cancer cell proliferation and induces mitochondrial apoptosis by modulating bax/bcl-2 family proteins levels (Zhao and He, 2015). By blocking NF-kB signaling pathway, Chidamide can inhibit cell proliferation and enhance drug sensitivity in multiple myeloma (Liu et al, 2019). Chidamide inhibits MDS and AML cells viability via JAK2/STAT3 signaling (Zhao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%